IP micro-mobility protocols. - Campbell, Andrew T. (Mobile computing and communications review.)
The IETF Mobile IP Working Group is discussing a number of enhancements to the base protocol to reduce the latency, packet loss and signaling overhead experienced during handoff. In this article, we discuss a number of "micro-mobility protocols" that extend Mobile IP with fast handoff and paging capabilities. The aim of this article is not to provide an exhaustive survey of these protocols. Rather, we discuss the motivation behind micro-mobility, present common characteristics that a number of proposals share and briefly describe some of the key contributions discussed by the working group. In the longer term there is a need to understand the differences between many of the micro-mobility proposals discussed in this article in terms of, complexity of the design choice, and performance differences. As part of that process we have recently made available the Columbia Micro-mobility Suite (CMS). The CMS software is freely available from the web (comet.columbia.edu/micromobility) and includes ns source code extensions for Cellular IP, Hawaii and Hierarchical Mobile IP.